2007
DOI: 10.1007/s11661-006-9071-8
|View full text |Cite
|
Sign up to set email alerts
|

The Transformation of Carbides during Austenization and Its Effect on the Wear Resistance of High Speed Steel Rolls

Abstract: The transformation of carbides with austenization time of a high speed steel (HSS) roll material, manufactured by a centrifugal casting method, has been studied. The correlation between wear resistance and the type, morphology, volume fraction, and distribution of the carbides has also been investigated. Microstructural observations, X-ray diffraction (XRD) analysis, hardness measurements, and energy dispersive spectroscopy (EDS) have been used to characterize the carbides. The type and volume fraction of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 11 publications
1
24
0
3
Order By: Relevance
“…According to our previous research, [1] the long-time austenization can bring about changes in the type, morphology, volume fraction, and distribution of the carbides, which results in an improvement of the roomtemperature wear resistance. In this study, we made the HSS roll with the similar chemical composition and found the same microstructure evolution with increased austenization time shown as follows.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…According to our previous research, [1] the long-time austenization can bring about changes in the type, morphology, volume fraction, and distribution of the carbides, which results in an improvement of the roomtemperature wear resistance. In this study, we made the HSS roll with the similar chemical composition and found the same microstructure evolution with increased austenization time shown as follows.…”
Section: Discussionmentioning
confidence: 90%
“…In this process, the overall carbide size decreases and the homogeneity of the carbide distribution increases. Consequently, the room-temperature wear resistance, [1] the high-temperature wear resistance, and the thermal fatigue properties are improved simultaneously. This finding should be of great use for the industrial production of HSS rolls and for the future improvement of properties of HSS rolls by controlling chemical composition, roller casting process, and the heat-treatment process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, relatively soft M 2 C particles (1700 to 1900 HV) [3] are replaced by hard MC particles (2400 to 2600 HV) [24] at high austenitizing temperatures.…”
Section: Effects Of Carbides On Wear Resistance and Crack Propagationmentioning
confidence: 99%
“…The HSS, which belongs to high carbon ledeburitic steel, contains more alloying elements such as W, Mo, Cr, V forming carbides including MC, M 2 C, M 6 C, M 7 C 3 and M 23 C 6 (Ref [10][11][12]. The extremely high hardness (HRC 63-70) can be obtained by special heat treatment, and the hardness and wear resistance can be retained up to 550-600℃ (Ref 13).…”
Section: Introductionmentioning
confidence: 99%